Enhancing evidence use in public health nutrition policymaking: theoretical insights from a New Zealand case study. Issue 1 (December 2016) - Field, P.; Gauld, R.; Lawrence, M.
Abstract Background Enhancing the use of evidence in policymaking is critical to addressing the global burden of nutrition-related disease. Whilst the public health nutrition community has embraced evidence-informed policymaking, their approach of defining relevant evidence and evaluating policy has not brought about major shifts in policymaking. This article uses a public health nutrition case study to refine a novel theory-informed framework for enhancing the use of evidence in government public health nutrition policymaking. Our aim is to contribute insights from evidence-informed policy to the emerging paradigm in public health nutrition policymaking. Methods An enquiry framework informed by three groups of theories underpinning evidence-informed policy was used to explore the role of socially mediated processes on the use of evidence. A public health nutrition case study on food marketing to New Zealand children was conducted to refine the framework. Interview data collected from 54 individuals representing four key policy stakeholder groups, policymakers, academics, and food industry and non-government organisations were analysed using deductive and inductive thematic analysis. To enhance theoretical robustness, an alternative hypothesis of political explanations for evidence use was explored alongside the enquiry framework. Results We found the prevailing political climate influenced the impact of advocacy for evidence inclusive processes at the meta-policy and policymaking process levels and in policy community relationships. Low levels of awareness of the impact of these processes on evidence use and uncoordinated advocacy resulted in the perpetuation of ad hoc policymaking. These findings informed refinements to the enquiry framework. Conclusion Our study highlights the role advocates can play in shifting government public health nutrition policymaking systems towards enhanced use of evidence. Our Advocacy for Evidence Use framework argues for a three-channel approach to advocacy for using evidence in the public interest. The framework provides a means for building a constituency for evidence use in public health nutrition and adds understanding about advocacy to the field of evidence-informed policy. Future research should examine the impact of coordinated advocacy on public health nutrition policymaking systems.